Strategies and policies from promoting the use of renewable energy resource in the UAE - Al-Amir, Jawaher (2013)
This paper looks into developing energy policy in the UAE in order to prompt renewable energy practices and thus sustainability in the UAE. This includes analyzing current and proposed future energy policies in the UAE. The research analyzed a wide range of strategies used in different countries in order to assess the best practice examples, while remaining mindful of the particularities of each country. Based on these lessons a strategy for promoting renewable energy in the UAE was formulated. The proposed strategy is composed of short, medium and long term policies. The proposed strategy was submitted to and discussed with relevant authorities and stakeholders in the UAE. Based on the feedback from the stakeholders the proposed policy was further refined. The main components of the final strategy include deregulation at three different levels (emirate, country and the gulf region), open access to the grid as well as financial incentives, e.g. implementation of a Feed-in Tariff. The final strategy is included at the end of the paper.